Electrolyte-resistant lithium battery special-shaped tape and preparation method thereof
By using a blended modified emulsion of styrene butadiene rubber and natural rubber combined with acrylic staple fibers and micro-fillers, electrolyte-resistant lithium battery special-shaped tape was prepared, which solved the problem that the existing tape could not meet the connection and insufficient corrosion resistance of different surface shapes, and achieved efficient bonding and electrolyte resistance.
Patent Information
- Application Number
- CN202310710486.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-15
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-06-15
AI Technical Summary
Existing lithium battery tapes cannot meet the connection requirements of different surface shapes and there is room for improvement in corrosion resistance and electrolyte resistance.
A blended modified emulsion of styrene butadiene rubber and natural rubber is used as the main body of the matrix elastomer, and combined with acrylic staple fibers, micro-fillers and functional additives to form electrolyte-resistant lithium battery special-shaped tape. The tape improves insulation and flame retardant through the uniform dispersion of micron fillers and the use of TPI, and enhances antioxidant and anti-aging properties through the addition of functional additives.
It realizes effective connections to objects in different spaces and three-dimensional shapes, has good adhesion, corrosion resistance and electrolyte resistance, and can maintain the structure stability in high temperature environments and avoid short circuits, leakage and liquid leakage.
Abstract
Description
Technical Field
[0001] The invention relates to an electrolyte-resistant lithium battery special-shaped adhesive tape and a preparation method thereof, belonging to the technical field of material preparation. Background Art
[0002] With the improvement of existing materials and battery design technology and the emergence of new materials, the application scope of lithium ions is constantly expanding. As one of the necessary materials in the production and manufacturing of lithium batteries, lithium battery tape has broad development prospects. Civilian use has expanded from mobile phones, PDA laptops, etc. in the information industry to energy transportation, electric vehicles, wind power station storage and other fields. Military use covers electronic equipment on land, sea and air weapons and equipment. Lithium-ion batteries provide supporting products for electronic products to provide power energy. In the future, it will be widely used in mobile communication tools and equipment, as well as electric vehicles and other fields, and its potential demand is huge.
[0003] At the same time, lithium battery tape is widely used in lithium-ion batteries to play the role of insulation and fixation. It is an indispensable and important material for lithium-ion batteries. In order to make lithium batteries have good stability under high temperature extreme conditions such as production and use, the use of tape needs to ensure that lithium batteries can maintain structural stability and unchanged chemical properties for a long time in high temperature environments, without short circuits, leakage, liquid leakage and other problems, and can adapt to various space bonding.
[0004] However, the existing tapes are all used for bonding two planes and belong to plane application tapes. They are not satisfied with the connection of different surfaces and are not limited to planes. There is still a lot of room for improvement in terms of corrosion resistance and electrolyte resistance. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide an electrolyte-resistant lithium battery-type special-shaped tape that can connect objects in different spaces and different three-dimensional shapes, has good adhesion, is not corroded and has good electrolyte resistance.
[0006] The second object of the present invention is to provide a method for preparing the above-mentioned electrolyte-resistant lithium battery special-shaped tape, using a blended modified emulsion of styrene-butadiene rubber and natural rubber as the main body of the base elastomer, and the micron filler is well and evenly dispersed without sedimentation in the chemical reaction, which is beneficial to the performance of insulation performance and further improves the electrolyte resistance of the special-shaped tape in lithium batteries.
[0007] The first object of the present invention can be achieved by adopting the following technical scheme: an electrolyte-resistant lithium battery special-shaped tape, the electrolyte-resistant lithium battery special-shaped tape comprising a base layer; the base layer is a three-dimensional shape; the base layer comprises the following effective ingredients in parts by weight:
[0008] Furthermore, the fiber length of the acrylic staple fiber is 1-6 mm.
[0009] Furthermore, the micron filler includes mica powder, micron silicon dioxide and micron zinc borate, and the mass ratio thereof is 10:(6-7):(0.8-1).
[0010] Furthermore, the functional additives include 1-2 parts of activator, 30-40 parts of carbon black, 0.8-1 parts of coupling agent, 0.5-0.7 parts of antioxidant, 0.3-0.6 parts of vulcanizing agent, 0-0.6 parts of antioxidant and 0.5-1 parts of accelerator based on the total weight of the base layer.
[0011] Further, the activator is at least one of vanadium acetylacetonate, tetramethylthiourea, triphenylphosphine, acetylacetone and n-butyraldehyde-aniline condensate 808 .
[0012] Further, the antioxidant is at least one of antioxidant 1010 , antioxidant MB and antioxidant 168 .
[0013] Furthermore, the electrolyte-resistant lithium battery special-shaped tape also includes an adhesive layer and a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom.
[0014] Furthermore, the effective ingredients of the adhesive layer include 80-100 parts by weight of styrene-butadiene latex, 15-25 parts by weight of polyisobutylene latex, 20-30 parts by weight of chloroprene latex, 5-10 parts by weight of zinc oxide and 10-30 parts by weight of terpene resin.
[0015] The second object of the present invention can be achieved by adopting the following technical scheme: a method for preparing an electrolyte-resistant lithium battery special-shaped tape, the preparation method comprising the steps of forming a substrate layer;
[0016] The steps of forming the base layer include:
[0017] Prefabrication step: dispersing acrylic staple fibers to obtain acrylic staple fiber pre-dispersed suspension;
[0018] The first mixing step is to mix the natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension and functional additives to obtain acrylic staple fiber masterbatch;
[0019] Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, micron filler and functional additives to obtain a masterbatch;
[0020] Three mixing steps: the masterbatch is cooled to room temperature, and then the functional additives are added to mix, discharge the glue, and shape it into a three-dimensional shape to obtain a base layer.
[0021] Furthermore, the method also includes the step of forming an adhesive layer: stirring styrene-butadiene latex with a pH value of 9-10 and chloroprene latex with a pH value of 9-10 at 300-320 r / min for 100-110 min, adding zinc oxide and terpene resin, mixing under the conditions of time 90-100 min, speed 30-50 r / min, and temperature 110-120° C., adding polyisobutylene latex and stirring for 16-20 min, filtering with a 150-mesh filter cloth, and forming on the substrate layer to obtain an adhesive layer.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The electrolyte-resistant lithium battery special-shaped adhesive tape of the present invention can connect objects in different spaces and different three-dimensional shapes, has good adhesion, is not corroded, and has good electrolyte resistance;
[0024] 2. The electrolyte-resistant lithium battery special-shaped adhesive tape of the present invention does not debond after being soaked in electrolyte and has good adhesion;
[0025] 3. The preparation method of the electrolyte-resistant lithium battery shaped tape of the present invention uses a blended modified emulsion of styrene-butadiene rubber and natural rubber as the main body of the base elastomer, and can be quickly self-cured at low temperature without adding a curing agent. It is supplemented with micron fillers and TPI, so that the prepared base layer has resilience, good tensile properties, and high adhesion performance, and can be well attached to the adhesive layer and cooperate with the adhesive layer, further improving the electrolyte resistance of the electrolyte-resistant lithium battery shaped tape and improving the safety factor of lithium batteries.
[0026] 4. The preparation method of the electrolyte-resistant lithium battery special-shaped adhesive tape of the present invention enables the micron filler to be well and evenly dispersed without settling, which is beneficial to the performance of insulation performance; and also improves the flame retardancy of the special-shaped substrate layer. DETAILED DESCRIPTION
[0027] Below, in conjunction with specific implementation modes, the present invention is further described:
[0028] A special-shaped adhesive tape for an electrolyte-resistant lithium battery, comprising a base layer, an adhesive layer and a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom; the base layer is a three-dimensional shape; the base layer comprises the following effective ingredients in parts by weight:
[0029] Among them, the fiber length of acrylic staple fiber is 1-6mm.
[0030] The micron filler includes mica powder, micron silicon dioxide and micron zinc borate, and the mass ratio thereof is 10:(6-7):(0.8-1).
[0031] After micron filler mica powder, micron silicon dioxide and micron zinc borate are mixed, they are ground through a 300 mesh sieve to obtain. The matrix layer with mica powder as the main micron filler has high insulation, but the density of mica powder is large, and it is easy to settle in the system. Although its anti-settling property can be improved by reducing the size of micron mica powder, the agglomeration phenomenon of micron particles is more serious as the particle diameter decreases, affecting its dispersion and performance. In addition, the above-mentioned micron filler is dispersed in the matrix layer structure, because the surface area is large and a network structure is formed in the system, so these micron fillers also further improve insulation and flame retardancy while balancing its cost.
[0032] The micron filler has high group activity and contains a large number of hydroxyl groups, which can form hydrogen bonds with the hydroxyl groups on the surface of TPI, so that the micron filler and TPI can be firmly combined to form a strong network structure in the matrix layer, improve the strength of the matrix layer, and enhance the adhesion performance of the three-dimensional matrix layer so that it can be permanently bonded to the adhesive layer.
[0033] Mica powder has good insulation properties and stable nature. Even if it is oxidized, its product, oxidized mica powder, still has good insulation properties.
[0034] The functional additives include 1-2 parts of activator, 30-40 parts of carbon black, 0.8-1 parts of coupling agent, 0.5-0.7 parts of antioxidant, 0.3-0.6 parts of vulcanizing agent, 0-0.6 parts of antioxidant and 0.5-1 parts of accelerator, based on the total weight of the base layer. The carbon black filler component has good fluidity and wettability, and can penetrate into cavities and cracks to make the inside of the rubber layer denser, thereby effectively inhibiting the volume shrinkage caused by colloid decomposition.
[0035] The activator is at least one of vanadium acetylacetonate, tetramethylthiourea, triphenylphosphine, acetylacetone and n-butyraldehyde-aniline condensate 808. The activator can promote the cross-linking of active groups in natural rubber and styrene-butadiene rubber and improve the cohesion of the base layer.
[0036] The antioxidant is at least one of antioxidant 1010, antioxidant MB and antioxidant 168, which can improve the anti-aging property of the base layer.
[0037] The vulcanizing agent is one of an amine-containing compound and a sulfur-containing resin compound.
[0038] The effective ingredients of the adhesive layer include 80-100 parts by weight of styrene-butadiene latex, 15-25 parts by weight of polyisobutylene latex, 20-30 parts by weight of chloroprene latex, 5-10 parts by weight of zinc oxide and 10-30 parts by weight of terpene resin.
[0039] Among them, the release layer is a double-sided release material with a release force of 30g / in, which can protect the viscosity of the adhesive layer and facilitate unwinding.
[0040] The preparation method of the electrolyte-resistant lithium battery special-shaped tape comprises the steps of forming a base layer, forming an adhesive layer on the base layer, and forming a release layer on the adhesive layer.
[0041] The steps of forming the base layer include:
[0042] Prefabrication step: placing the acrylic staple fibers and the operating oil in a stirring kettle and stirring them evenly to disperse them, thereby obtaining a pre-dispersed suspension of the acrylic staple fibers;
[0043] The first mixing step is to add natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension, activator and vulcanizer into an internal mixer for mixing to obtain acrylic staple fiber masterbatch;
[0044] Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, carbon black, antioxidant and micron filler to obtain a masterbatch;
[0045] Three mixing steps: the masterbatch is cooled to room temperature, and then a coupling agent, a accelerator and an antioxidant are added to mix, discharge the glue, and shape it into a three-dimensional shape to obtain a base layer.
[0046] The process oil is an alkyl softener.
[0047] The step of forming the adhesive layer comprises: adjusting the pH value of styrene-butadiene latex emulsion to 9-10 with ammonia water and adjusting the pH value of chloroprene latex emulsion to 9-10 with a 5wt% dilute boric acid solution; stirring for 100-110 minutes at 300-320r / min, adding zinc oxide and terpene resin, kneading under the conditions of time 90-100min, speed 30-50r / min, and temperature 110-120°C, adding polyisobutylene latex and stirring for 16-20min, filtering with a 150-mesh filter cloth, and forming on a substrate layer to obtain an adhesive layer.
[0048] Styrene butadiene latex contains carboxylic acid, which increases the polarity of the molecular chain and thus improves its adhesion. Styrene butadiene latex is low in cost and environmentally friendly and safe, but it still has problems such as slow drying speed, poor initial adhesion, poor insulation performance, and stability that needs to be further improved.
[0049] The three-dimensional base layer uses a blended modified emulsion of styrene-butadiene rubber and natural rubber as the main body of the base elastomer. It does not need to add a curing agent. Through the activator in the component, it can be quickly self-cured at low temperature. Assisted by carbon black filler, micron filler and TPI, the prepared three-dimensional base layer has resilience, good tensile properties, and high adhesion performance. It can adhere to the adhesive layer well and soak in the electrolyte for a long time without damage. By cooperating with the adhesive layer, the electrolyte resistance of the special-shaped tape in the lithium battery can be further improved, and the safe use factor of the lithium battery can be improved; at the same time, through the trace addition of antioxidants and vulcanizers, the three-dimensional base layer is given good corrosion resistance and aging resistance; the preparation method of acrylic staple fibers, coupling agents, and micron fillers can ensure that the micron fillers in the three-dimensional base layer are well and evenly dispersed without sedimentation, which is beneficial to the performance of insulation performance; the filling of micron fillers and mica powder particles with good flame retardant properties also improves the flame retardancy of the special-shaped tape. Electrolyte-resistant lithium battery special-shaped tape has good electrolyte corrosion resistance and bonding performance. It can maintain a high peeling force without debonding in long-term immersion in electrolyte, thus ensuring the safety performance of lithium batteries. Example
[0050] Electrolyte-resistant lithium battery special-shaped tape, the electrolyte-resistant lithium battery special-shaped tape comprises a base layer, an adhesive layer and a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom; the base layer is a three-dimensional shape; the effective components and weight parts of the base layer are shown in Table 1:
[0051] Table 1 Active ingredients of the base layer
[0052] Element Weight Natural rubber 75 servings Styrene Butadiene Rubber 15 servings TPI 8 servings Acrylic staple fiber 6 servings Micron Filler 9 servings Vanadium acetylacetonate 40 servings Carbon Black 38 servings Coupling agent 0.85 Antioxidant 1010 0.65 Vulcanizing agent 0.4 parts Antioxidant 0.2 parts Accelerator 0.6 parts
[0053] The fiber length of the acrylic staple fiber is 3 mm.
[0054] The micron filler comprises mica powder, micron silicon dioxide and micron zinc borate in a mass ratio of 10:6.5:0.85, and the preparation method is the same as the specific implementation manner.
[0055] The adhesive layer includes 85 parts of styrene-butadiene latex, 16 parts of polyisobutylene latex, 28 parts of chloroprene latex, 8 parts of zinc oxide and 22 parts of terpene resin in parts by weight.
[0056] The release layer is a double-sided release material with a release force of 30g / in.
[0057] The preparation method of the electrolyte-resistant lithium battery special-shaped tape comprises the steps of forming a base layer, forming an adhesive layer on the base layer, and forming a release layer on the adhesive layer.
[0058] The steps of forming the base layer include:
[0059] Prefabrication step: placing the acrylic staple fibers and the operating oil in a stirring kettle and stirring them evenly to disperse them, thereby obtaining a pre-dispersed suspension of the acrylic staple fibers;
[0060] The first mixing step is to add natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension, activator and vulcanizer into an internal mixer for mixing to obtain acrylic staple fiber masterbatch;
[0061] Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, carbon black, antioxidant and micron filler to obtain a masterbatch;
[0062] Three mixing steps: the masterbatch is cooled to room temperature, and then a coupling agent, a accelerator and an antioxidant are added to mix, discharge the glue, and shape it into a three-dimensional shape to obtain a base layer.
[0063] The process oil is an alkyl softener.
[0064] The step of forming the adhesive layer includes: adjusting the pH value of styrene-butadiene latex emulsion to 9-10 with ammonia water and adjusting the pH value of chloroprene latex emulsion to 9-10 with a 5wt% dilute boric acid solution; stirring for 105 minutes at 310r / min, adding zinc oxide and terpene resin, kneading under the conditions of time 95min, speed 45r / min, and temperature 115°C, adding polyisobutylene latex and stirring for 18min, filtering with a 150-mesh filter cloth, and forming on the substrate layer to obtain the adhesive layer. Example
[0065] Electrolyte-resistant lithium battery special-shaped tape, the electrolyte-resistant lithium battery special-shaped tape comprises a base layer, an adhesive layer and a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom; the base layer is a three-dimensional shape; the effective components and weight parts of the base layer are shown in Table 2:
[0066] Table 2 Active ingredients of the base layer
[0067] Element Weight Natural rubber 78 servings Styrene Butadiene Rubber 13 servings TPI 9 servings Acrylic staple fiber 6 servings Micron Filler 8 servings Butyraldehyde-aniline condensate 808 35 servings Carbon Black 38 servings Coupling agent 0.9 parts Antioxidant MB 0.6 parts Vulcanizing agent 0.4 parts Antioxidant 0.4 parts Accelerator 0.7 parts
[0068] The fiber length of acrylic staple fiber is 5 mm;
[0069] The micron filler comprises mica powder, micron silicon dioxide and micron zinc borate in a mass ratio of 10:6.8:0.9, and the preparation method is the same as that in the specific implementation manner.
[0070] The adhesive layer includes 90 parts of styrene-butadiene latex, 20 parts of polyisobutylene latex, 28 parts of chloroprene latex, 7 parts of zinc oxide and 28 parts of terpene resin in parts by weight.
[0071] The release layer is a double-sided release material with a release force of 30g / in.
[0072] The preparation method of the electrolyte-resistant lithium battery special-shaped tape comprises the steps of forming a base layer, forming an adhesive layer on the base layer, and forming a release layer on the adhesive layer.
[0073] The steps of forming the base layer include:
[0074] Prefabrication step: placing the acrylic staple fibers and the operating oil in a stirring kettle and stirring them evenly to disperse them, thereby obtaining a pre-dispersed suspension of the acrylic staple fibers;
[0075] The first mixing step is to add natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension, activator and vulcanizer into an internal mixer for mixing to obtain acrylic staple fiber masterbatch;
[0076] Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, carbon black, antioxidant and micron filler to obtain a masterbatch;
[0077] Three mixing steps: the masterbatch is cooled to room temperature, and then a coupling agent, a accelerator and an antioxidant are added to mix, discharge the glue, and shape it into a three-dimensional shape to obtain a base layer.
[0078] The process oil is an alkyl softener.
[0079] The step of forming the adhesive layer includes: adjusting the pH value of styrene-butadiene latex emulsion to 9-10 with ammonia water and adjusting the pH value of chloroprene latex emulsion to 9-10 with a 5wt% dilute boric acid solution; stirring for 105 minutes at 305r / min, adding zinc oxide and terpene resin, mixing under the conditions of time 95min, speed 45r / min, and temperature 115°C, adding polyisobutylene latex and stirring for 18min, filtering with a 150-mesh filter cloth, and forming on the base layer to obtain the adhesive layer. Example
[0080] Electrolyte-resistant lithium battery special-shaped tape, the electrolyte-resistant lithium battery special-shaped tape comprises a base layer, an adhesive layer and a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom; the base layer is a three-dimensional shape; the effective components and weight parts of the base layer are shown in Table 3:
[0081] Table 3 Active ingredients of the base layer
[0082] Element Weight Natural rubber 60 servings Styrene Butadiene Rubber 17 servings TPI 9 servings Acrylic staple fiber 5 servings Micron Filler 7 servings Tetramethylthiourea 43 servings Carbon Black 31 servings Coupling agent 0.95 copies Antioxidant 1010 0.55 serving Vulcanizing agent 0.5 serving Antioxidant 0.5 serving Accelerator 0.8 parts
[0083] The fiber length of acrylic staple fiber is 2 mm;
[0084] The micron filler comprises mica powder, micron silicon dioxide and micron zinc borate in a mass ratio of 10:6.5:0.9, and the preparation method is the same as that in the specific implementation manner.
[0085] The adhesive layer includes 95 parts of styrene-butadiene latex, 16 parts of polyisobutylene latex, 23 parts of chloroprene latex, 8 parts of zinc oxide and 16 parts of terpene resin in parts by weight.
[0086] The release layer is a double-sided release material with a release force of 30g / in.
[0087] The preparation method of the electrolyte-resistant lithium battery special-shaped tape comprises the steps of forming a base layer, forming an adhesive layer on the base layer, and forming a release layer on the adhesive layer.
[0088] The steps of forming the base layer include:
[0089] Prefabrication step: placing the acrylic staple fibers and the operating oil in a stirring kettle and stirring them evenly to disperse them, thereby obtaining a pre-dispersed suspension of the acrylic staple fibers;
[0090] The first mixing step is to add natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension, activator and vulcanizer into an internal mixer for mixing to obtain acrylic staple fiber masterbatch;
[0091] Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, carbon black, antioxidant and micron filler to obtain a masterbatch;
[0092] Three mixing steps: the masterbatch is cooled to room temperature, and then a coupling agent, a accelerator and an antioxidant are added to mix, discharge the glue, and shape it into a three-dimensional shape to obtain a base layer.
[0093] The process oil is an alkyl softener.
[0094] The step of forming the adhesive layer includes: adjusting the pH value of styrene-butadiene latex emulsion to 9-10 with ammonia water and adjusting the pH value of chloroprene latex emulsion to 9-10 with a 5wt% dilute boric acid solution; stirring for 109 minutes under the stirring condition of 315r / min, then adding zinc oxide and terpene resin, kneading under the conditions of time 95min, speed 45r / min, and temperature 115°C, then adding polyisobutylene latex and stirring for 18min, filtering with a 150-mesh filter cloth, and forming on the base layer to obtain the adhesive layer.
[0095] Performance Testing:
[0096] The insulation properties of Examples 1-3 were tested using a SB100A four-probe insulation tester.
[0097] Experiments show that the insulation performance of the matrix layer increases with the increase of the amount of mixed filler added, and its percolation threshold is only 5wt%. At this time, the insulation of the matrix layer is 15.79S / cm, which is two orders of magnitude higher than the insulation of the matrix layer filled only with mica powder flakes, and the heterogeneous matrix has good heat resistance and stability.
[0098] In Example 1-3, the solvent resistance performance was tested by placing the tape in an electrolyte at a simulated high temperature of more than 50°C for 3 days to test the debonding and peeling strength. For comparison, a traditional ordinary tape was selected for the same condition experiment. The experimental data is shown in Table 4.
[0099] Table 4 Solvent resistance test
[0100] It can be seen that Example 3 has excellent solvent resistance, which is significantly improved over the performance of traditional adhesive tapes.
[0101] For those skilled in the art, various other corresponding changes and modifications can be made according to the technical solutions and concepts described above, and all of these changes and modifications should fall within the protection scope of the claims of the present invention.
Claims
1. An electrolyte-resistant lithium battery special-shaped tape, characterized in that: The electrolyte-resistant lithium battery special-shaped tape comprises a base layer and an adhesive layer; the effective components of the adhesive layer include 80-100 parts by weight of styrene-butadiene latex, 15-25 parts by weight of polyisobutylene latex, 20-30 parts by weight of chloroprene latex, 5-10 parts by weight of zinc oxide and 10-30 parts by weight of terpene resin; the base layer is a three-dimensional shape; the base layer comprises the following effective components by weight: Natural rubber 50-80 parts; Styrene butadiene rubber 12-20 parts; TPI 7-10 copies; 4-7 parts of acrylic staple fiber; 7-10 parts of micron filler; 32-45 parts of functional additives; The micron filler comprises mica powder, micron silicon dioxide and micron zinc borate, and the micron filler passes through a 300-mesh sieve, and the mass ratio thereof is 10:(6-7):(0.8-1).
2. The electrolyte-resistant lithium battery shaped tape according to claim 1, characterized in that: The fiber length of the acrylic staple fiber is 1-6 mm.
3. The electrolyte-resistant lithium battery shaped tape according to claim 1, characterized in that: The functional additives include, based on the total weight of the substrate layer, 1-2 parts of an activator, 30-40 parts of carbon black, 0.8-1 parts of a coupling agent, 0.5-0.7 parts of an antioxidant, 0.3-0.6 parts of a vulcanizing agent, 0-0.6 parts of an antioxidant and 0.5-1 parts of an accelerator.
4. The electrolyte-resistant lithium battery special-shaped adhesive tape according to claim 3, characterized in that: The activator is at least one of vanadium acetylacetonate, tetramethylthiourea, triphenylphosphine, acetylacetone and n-butyraldehyde-aniline condensate 808 .
5. The electrolyte-resistant lithium battery shaped adhesive tape according to claim 3, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant MB and antioxidant 168 .
6. The electrolyte-resistant lithium battery special-shaped adhesive tape according to claim 1, characterized in that: The electrolyte-resistant lithium battery special-shaped tape also includes a release layer; the release layer, the adhesive layer and the base layer are stacked in sequence from top to bottom.
7. A method for preparing an electrolyte-resistant lithium battery special-shaped adhesive tape as claimed in claim 3, characterized in that: The preparation method comprises the steps of forming a substrate layer; The step of forming the base layer comprises: Prefabrication step: dispersing acrylic staple fibers to obtain acrylic staple fiber pre-dispersed suspension; The first mixing step is to mix the natural rubber, styrene-butadiene rubber, acrylic staple fiber pre-dispersed suspension, activator and vulcanizing agent to obtain acrylic staple fiber masterbatch; Secondary mixing step: mixing acrylic staple fiber masterbatch, TPI, micron filler, carbon black and antioxidant to obtain a masterbatch; Three mixing steps: cooling the masterbatch to room temperature, then adding a coupling agent, an accelerator, and an antioxidant to mix, discharge the masterbatch, and shape it into a three-dimensional shape to obtain a base layer.
8. The method for preparing the electrolyte-resistant lithium battery special-shaped adhesive tape according to claim 7, characterized in that: The method also includes the step of forming an adhesive layer: stirring styrene-butadiene latex with a pH value of 9-10 and chloroprene latex with a pH value of 9-10 at 300-320 r / min for 100-110 min, adding zinc oxide and terpene resin, mixing under the conditions of 90-100 min, 30-50 r / min and 110-120° C., adding polyisobutylene latex and stirring for 16-20 min, filtering with a 150-mesh filter cloth, and forming on the substrate layer to obtain an adhesive layer.
Citation Information
Patent Citations
3D special-shaped adhesive tape
CN109233657A
Electrolyte-resistant ethylene propylene diene monomer and preparation method thereof
CN112920517A